Azwar Anas and Innovation in Local Government: A Phronesis Leadership Study - Bima Katangga (Iapa Proceedings Conference, 2019)
Phronesis leadership is the extraction of Aristotle's philosophy which involves judgment from the individual leader in determining the good value of reality. This article aims to analyze leadership practice in developing countries, qualitatively using 6 criteria of Nonaka's et al (2018) frameworks. The purpose of this article is to find out how Azwar Anas's phronesis leadership in Banyuwangi, Indonesia, can produce service innovations such as the "Lahir Procot Pulang Bawa Akta" program and Banyuwangi Ethno Carnival (BEC) and observe the dynamic process that arises. The results of this study indicate that Azwar Anas succeeded in expressing 'common good' by understanding reality and using his political abilities to influence the organization and its population, creating 'Ba', and articulating the desirable future.